Berry phase quantum thermometer - Martin-Martinez, Eduado; Dragan, Andrzej; Mann, Robert B.; Fuentes, Ivette (IOP Publishing, 2013)
We show how the Berry phase can be used to construct a high-precision quantum thermometer. An important advantage of our scheme is that there is no need for the thermometer to acquire thermal equilibrium with the sample. This reduces measurement times and avoids precision limitations.